Chapter Assessing the Performance of Personal Protective Equipment1 - Kechagiadakis, Georgios (InTechOpen, 2017)
Schistosomiasis is the second most prevalent parasitic disease in the world. Currently, the treatment of this disease relies on a single drug, praziquantel, and due to the identification of resistant parasites, the development of new drugs is urged. The demand for the development of robust high‐throughput parasite screening techniques is increasing as drug discovery research in schistosomiasis gains significance. Here, we review the most common methods used for compound screening in the parasites life stages and also summarize some of the methods that have been recently developed. In addition, we reviewed the methods most commonly implemented to search for promising targets and how they have been used to validate new targets against the parasite Schistosoma mansoni. We also review some promising targets in this parasite and show the main approaches and the major advances that have been achieved by those studies. Moreover, we share our experiences in schistosomiasis drug discovery attained with our S. mansoni drug screening platform establishment.